A kind of three-silver temperable three-property gray Low-E glass
By compounding multiple layers of film on the glass substrate, the problem of the existing three-silver Low-E glass being unable to achieve three-dimensional gray and having color difference is solved, achieving an overall three-character gray appearance and no color difference, and improving the artistic effect of the glass. and user experience.
Patent Information
- Application Number
- CN202010208304.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-03-23
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2040-03-23
AI Technical Summary
The existing three-silver Low-E glass cannot achieve tri-sex gray, and there are large color differences on the front and sides, which affects the appearance and user experience of the glass.
By sequentially compounding fourteen film layers on the glass substrate from the inside to the outside, including ZrO2, Nb2O5, AZO, Ag, NiCr and other materials, and setting a reasonable film thickness to ensure that the overall appearance of the glass appears three-dimensional gray, and ensure that there is no Color difference.
It achieves the three-character gray appearance of Low-E glass, eliminates the color difference between the front and side, enhances the artistic effect and user experience of the glass, and improves the market competitiveness of the product.
Smart Images

Figure CN111196683B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of glass manufacturing, and in particular relates to a three-silver temperable three-property gray Low-E glass. Background Art
[0002] Glass is an important building material. Most modern high-rise buildings use glass curtain walls. With the continuous development of glass deep processing, architectural glass has gradually been replaced by energy-saving and environmentally friendly low-radiation Low-E glass instead of the original single-piece glass. However, the current triple-silver Low-E glass cannot achieve the three-property gray, and there is a large color difference between the front and side of the Low-E glass, resulting in inconsistent colors, affecting the appearance of the glass and poor user experience. Summary of the invention
[0003] (I) Purpose of the invention
[0004] In order to overcome the above shortcomings, the purpose of the present invention is to provide a triple-silver tempered tri-gray Low-E glass to solve the technical problems that the existing Low-E glass cannot achieve tri-gray and has a large color difference between the front and side, affecting the appearance of the glass.
[0005] (II) Technical solution
[0006] To achieve the above objectives, the technical solutions provided by this application are as follows:
[0007] A three-silver temperable three-property gray Low-E glass comprises: a glass substrate, on which fourteen film layers are compounded in sequence from the inside to the outside, wherein the first film layer, i.e., the innermost film layer, is a ZrO2 layer, the second film layer is a Nb2O5 layer, the third film layer is an AZO layer, the fourth film layer is an Ag layer, the fifth film layer is a NiCr layer, the sixth film layer is an AZO layer, the seventh film layer is an Ag layer, the eighth film layer is a NiCr layer, the ninth film layer is an AZO layer, the tenth film layer is an Ag layer, and the eleventh film layer is a NiCr layer. The first film layer is a NiCr layer, the twelfth film layer is an AZO layer, the thirteenth film layer is a Si3N4 layer, the fourteenth film layer is ZrO2, the fourth film layer Ag layer has a thickness of 9 to 12 nm, the fifth film layer NiCr layer has a thickness of 1 to 3 nm, the seventh film layer is an Ag layer with a thickness of 15 to 17 nm, the eighth film layer NiCr layer has a thickness of 2.5 to 3.5 nm, the tenth film layer Ag layer has a thickness of 3.5 to 5.5 nm, and the eleventh film layer NiCr layer has a thickness of 2 to 4 nm.
[0008] Furthermore, the thickness of the first film layer, ie, the innermost film layer, the ZrO2 layer, is 35 to 50 nm, and the thickness of the fourteenth film layer, the ZrO2 layer, is 45 to 35 nm.
[0009] Furthermore, the thickness of the second film layer Nb2O5 is 11-13 nm.
[0010] Furthermore, the thickness of the third film layer AZO layer is 5-7 nm.
[0011] Furthermore, the thickness of the sixth film layer AZO layer is 110-115 nm.
[0012] Furthermore, the thickness of the ninth film layer, the AZO layer, is 40-43 nm.
[0013] Furthermore, the thickness of the twelfth film layer, the AZO layer, is 68-73 nm.
[0014] Furthermore, the thickness of the thirteenth film layer Si3N4 is 75-80 nm.
[0015] Furthermore, the thickness of the fourteenth film layer Si3N4 is 35-40 nm.
[0016] By means of the above technical scheme, the beneficial effects of the present application are as follows: the three-silver tempered three-property gray Low-E glass is obtained by sequentially and adjacently compounding the first film layer ZrO2 layer, the second film layer Nb2O5 layer, the third film layer AZO layer, the fourth film layer Ag layer, the fifth film layer NiCr layer, the sixth film layer AZO layer, the seventh film layer Ag layer, the eighth film layer NiCr layer, the ninth film layer AZO layer, the tenth film layer Ag layer, and the eleventh film layer NiCr layer on a glass substrate from inside to outside. The twelfth film layer is an AZO layer, the thirteenth film layer is a Si3N4 layer, the fourteenth film layer is ZrO2, and the thickness of the fourth film layer Ag layer is 9-12nm, the thickness of the fifth film layer NiCr layer is 1-3nm, the thickness of the seventh film layer Ag layer is set to 15-17nm, the thickness of the eighth film layer NiCr layer is set to 2.5-3.5nm, the thickness of the tenth film layer is set to 3.5-5.5nm, and the thickness of the eleventh film layer is set to 2-4nm. The thicknesses of the fourth film layer, the fifth film layer, the seventh film layer, the eighth film layer, the tenth film layer and the eleventh film layer are designed so that the overall appearance of the Low-E glass product of the present invention presents three-property gray, and by setting the second film layer Nb2O5 layer, Nb2O5 has the characteristics of high anti-discoloration ability, high refractive index and high stability, which ensures that the Low-E glass has no color difference, and the color of the glass is consistent whether it is viewed from the front or the side, which increases the artistic effect of the Low-E glass, meets the aesthetic requirements of high-end buildings, improves the user experience, and improves the competitiveness of the product in the market. The Ag layer and AZO layer set in the present application can shield a large amount of infrared radiation from the sun, so that the Low-E glass of the present application isolates solar energy. By setting the TiO2 layer, the ZrO2 layer, the Si3N4 layer and the NiCr layer, a high-hardness protective layer can be formed, so that the Low-E glass has high hardness and strong corrosion resistance, and the mechanical properties of the glass are better, and the Low-E glass is not easily scratched or worn. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 It is a schematic structural diagram of the triple-silver temperable triple-gray Low-E glass of the present invention.
[0018] Reference numerals:
[0019] 1: glass substrate; 21: first film layer; 22: second film layer; 23: third film layer; 24: fourth film layer; 25: fifth film layer; 26: sixth film layer; 27: seventh film layer; 28: eighth film layer; 29: ninth film layer; 210: tenth film layer; 211: eleventh film layer; 212: twelfth film layer; 213: thirteenth film layer; 214: fourteenth film layer. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments and with reference to the accompanying drawings. It should be understood that these descriptions are only exemplary and are not intended to limit the scope of the present invention. In addition, in the following description, the description of well-known structures and technologies is omitted to avoid unnecessary confusion of the concept of the present invention.
[0021] The present invention provides a three-silver temperable three-property gray Low-E glass, comprising: a glass substrate 1, on which fourteen film layers are compounded in sequence from the inside to the outside, wherein the first film layer 21, i.e., the innermost film layer, is a ZrO2 layer, the second film layer 22 is a Nb2O5 layer, the third film layer 23 is an AZO layer, the fourth film layer 24 is an Ag layer, the fifth film layer 25 is a NiCr layer, the sixth film layer 26 is an AZO layer, the seventh film layer 27 is an Ag layer, the eighth film layer 28 is a NiCr layer, the ninth film layer 29 is an AZO layer, the tenth film layer 210 is an Ag layer, and the eleventh film layer 211 is a NiCr layer. The twelfth film layer 212 is an AZO layer, the thirteenth film layer 213 is a Si3N4 layer, the fourteenth film layer 214 is a ZrO2 layer, the fourth film layer 24 (Ag layer) has a thickness of 9 to 12 nm, the fifth film layer 25 (NiCr layer) has a thickness of 1 to 3 nm, the seventh film layer 27 (Ag layer) has a thickness of 15 to 17 nm, the eighth film layer 28 (NiCr layer) has a thickness of 2.5 to 3.5 nm, the tenth film layer 210 (Ag layer) has a thickness of 3.5 to 5.5 nm, and the eleventh film layer 211 (NiCr layer) has a thickness of 2 to 4 nm.
[0022] The three-silver temperable three-property gray Low-E glass of the present application is compounded with a ZrO2 layer, a Nb2O5 layer, an AZO layer, an Ag layer, a NiCr layer, an AZO layer, an Ag layer, a NiCr layer, an AZO layer, an Ag layer, a NiCr layer, an AZO layer, a Si3N4 layer and a ZrO2 layer on a glass substrate 1 from the inside to the outside, and the thickness of the fourth film layer 24 (Ag layer) is 9 to 12 nm, the thickness of the fifth film layer 25 (NiCr layer) is 1 to 3 nm, and the thickness of the The thickness of the seventh film layer 27 (Ag layer) is set to 15-17 nm, the thickness of the eighth film layer 28 (NiCr layer) is set to 2.5-3.5 nm, the thickness of the tenth film layer 210 (Ag layer) is set to 3.5-5.5 nm, and the thickness of the eleventh film layer 211 is set to 2-4 nm. By reasonably designing the fourth film layer 24, the fifth film layer 25, the seventh film layer 27, the eighth film layer 28, the tenth film layer 210 (Ag layer) and the eleventh film layer 211 (NiCr layer), the thickness of the seventh film layer 27 (Ag layer) is set to 15-17 nm, the thickness of the eighth film layer 28 (NiCr layer) is set to 2.5-3.5 nm, the thickness of the tenth film layer 210 (Ag layer) is set to 3.5-5.5 nm, and the thickness of the eleventh film layer 211 is set to 2-4 nm. The thickness ratio of the TiO2 layer to the Nb2O5 layer makes the overall appearance of the Low-E glass product of the present invention present a tri-gray color, which increases the artistic effect of the Low-E glass, meets the aesthetic requirements of high-end buildings, improves the user experience, and improves the competitiveness of the product in the market. In addition, by setting the second film layer 22 (Nb2O5 layer), Nb2O5 has the characteristics of high anti-discoloration ability, high refractive index and high stability, which ensures that the Low-E glass has no color difference. Whether the glass is viewed from the front or the side, the color is consistent. In addition, the Ag and AZO of the present application can shield a large amount of infrared radiation from the sun, so that the Low-E glass of the present application isolates solar energy and avoids heat exchange between indoor and outdoor environments through the glass, thereby achieving a good heat insulation effect and improving indoor comfort. When the air conditioner is cooling or heating, after the indoor temperature reaches the set temperature, the air conditioner can be in standby mode for a longer time, thereby saving power consumption. In addition, the TiO2 layer can effectively prevent the indoor temperature from being too high, and the temperature of the Low-E glass can reach 400 °C. 2、 ZrO 2、 Si3N4 and NiCr are both high-hardness materials that can form a high-hardness protective layer, making the Low-E glass hard and corrosion-resistant, and making the glass have better mechanical properties. The Low-E glass is not easily scratched or worn. Furthermore, the Low-E glass of the present application can also increase the transmittance of visible light, thereby improving the indoor lighting effect and reducing the reflectivity of visible light, thereby reducing light pollution.
[0023] The specific functions of each film layer of the triple-silver tempered Low-E glass of this application and the specific thickness settings of each film layer are as follows:
[0024] The first film layer 21 (ZrO2 layer), that is, the zirconium dioxide layer, serves as the first dielectric layer and the first protective layer. ZrO2 is a material with high hardness, high density and antioxidant properties. It can improve the physical properties and antioxidant properties of the film layer, enhance the strength of the Low-E glass, prevent the glass from being worn and scratched, and prevent oxygen from entering the Ag oxide layer. The thickness of the first film layer 21 (ZrO2 layer) is set to 35 to 50 nm, preferably 38 nm.
[0025] The second film layer 22 (Nb2O5 layer), i.e., the niobium pentoxide layer, Nb2O5 serves as the second dielectric layer and the first barrier layer. In addition to reducing the discoloration of the Low-E glass at different angles and making the color deviation of the triple-silver Low-E glass small, Nb2O5 can also block the Na+ on the surface of the glass substrate 1 from entering the first functional layer Ag layer to destroy the silver layer. The second film layer 22 (Nb2O5 layer) can also reduce the reflectivity of visible light and avoid light pollution caused by a large amount of visible light reflection. The thickness of the second film layer 22 (Nb2O5 layer) is set to 11-13nm, preferably 12nm.
[0026] The third film layer 23 (AZO layer), i.e., the aluminum-doped zinc oxide layer, serves as the third dielectric layer and the second barrier layer. AZO is a material with high thermal stability and low infrared emissivity, which can prevent outdoor high temperatures from being transmitted to the indoors through radiation, and has a good heat insulation effect. The third film layer 23 (AZO layer) can also prevent high temperatures from damaging the fourth film layer 24 (Ag layer). The thickness of the third film layer 23 (AZO layer) is 5 to 7 nm, preferably 6 nm.
[0027] The fourth film layer 24 (Ag layer), that is, the metallic silver layer, is used as the first functional layer. Using silver as the coating layer can improve the infrared reflectivity of the film layer. Moreover, metallic silver has low infrared emissivity and has good heat insulation effect, which plays a role in environmental protection and energy saving. The preferred thickness of the fourth film layer 24 (Ag layer) is 10nm.
[0028] The fifth film layer 25 (NiCr layer) serves as a protective layer and flattening layer for the Ag layer. NiCr is a high-strength and corrosion-resistant alloy material with good chemical stability and thermal properties. It can protect the Ag layer from being damaged and prevent the Ag layer from being oxidized, thereby improving the mechanical strength and corrosion resistance of the Low-E glass of the present application. The preferred thickness of the fifth film layer 25 (NiCr layer) is 2 nm.
[0029] The sixth film layer 26 (AZO layer), that is, the aluminum-doped zinc oxide layer, serves as the fourth dielectric layer and the third barrier layer. It has low infrared emissivity and good heat insulation effect. The sixth film layer 26 (AZO layer) and the third film layer 23 (AZO layer) complement each other and can provide heat insulation protection for the fourth film layer 24 (Ag layer) from both sides to avoid damage to the fourth film layer 24 (Ag layer) due to high temperature. The thickness of the sixth film layer 26 (AZO layer) is 110-115nm, preferably 113nm.
[0030] The seventh film layer 27 (Ag layer), that is, the metallic silver layer, serves as the second functional layer. Using silver as the coating layer can improve the infrared reflectivity of the film layer. The metallic silver has a low emissivity and has a good heat insulation effect. The seventh film layer 27 (Ag layer) interacts with the fourth film layer 24 (Ag layer) to further reduce the emissivity of the Low-E glass, thereby playing a role in environmental protection and energy saving. The preferred thickness of the seventh film layer 27 (Ag layer) is 16 nm.
[0031] The eighth film layer 28 (NiCr layer), i.e., the nickel alloy layer, serves as the fourth barrier layer. NiCr is a high-strength and corrosion-resistant alloy material with good chemical stability and thermal properties. It can protect the Ag layer from being damaged and prevent the Ag layer from being oxidized, and can improve the strength and corrosion resistance of the Low-E glass of the present application. The eighth film layer 28 (NiCr layer) interacts with the fifth film layer 25 (NiCr layer) to provide corrosion protection to the seventh film layer 27 (Ag layer) from two directions. The thickness of the eighth film layer 28 (NiCr layer) is preferably 1.55 nm. The eighth film layer 28 (NiCr layer) can improve the thermal insulation performance of the Low-E glass.
[0032] The ninth film layer 29 (AZO layer), that is, the aluminum-doped zinc oxide layer, serves as the fifth dielectric layer and the fifth barrier layer. It has low infrared emissivity and good heat insulation effect. The ninth film layer 29 (AZO layer) complements the sixth film layer 26 (AZO layer) to provide heat insulation protection for the seventh film layer 27 (Ag layer) from both sides. The thickness of the ninth film layer 29 (AZO layer) is 40 to 43 nm.
[0033] The tenth film layer 210 (Ag layer), that is, the metallic silver layer, uses silver as a coating layer to improve the infrared reflectivity of the film layer. The tenth film layer 210 (Ag layer) has multiple functions with the seventh film layer 27 (Ag layer) and the fourth film layer 24 (Ag layer) to greatly reduce the emissivity of the Low-E glass, thereby playing a role in environmental protection and energy saving. The preferred thickness of the tenth film layer 210 (Ag layer) is 5.5 nm.
[0034] The eleventh film layer 211 (NiCr layer), that is, the nickel alloy layer, serves as the sixth barrier layer. NiCr is a high-strength and corrosion-resistant alloy material with good stability and thermal properties. It can improve the strength and corrosion resistance of the Low-E glass and improve the thermal insulation effect of the Low-E glass. The eleventh film layer 211 (NiCr layer) interacts with the eighth film layer 28 (NiCr layer) to provide thermal insulation and corrosion resistance protection to the tenth film layer 210 (Ag layer) from both sides. The preferred thickness of the eleventh film layer 211 (NiCr layer) is 3 nm.
[0035] The twelfth film layer 212 (AZO layer), i.e., the aluminum-doped zinc oxide layer, serves as the sixth dielectric layer and the seventh barrier layer, has a low infrared emissivity and has a good heat-insulating effect. It complements the ninth film layer 29 (AZO layer) and provides heat-insulating protection to the tenth film layer 210 (Ag layer) from both sides. The thickness of the twelfth film layer 212 (AZO layer) is 68 to 73 nm, preferably 70 nm.
[0036] The thirteenth film layer 213 (Si3N4 layer), i.e., the silicon nitride layer, is used as the second protective layer. Si3N4 is a material with high hardness and good oxidation resistance. It improves the physical properties and oxidation resistance of the film layer to enhance the strength of the Low-E glass and make the Low-E glass less susceptible to wear and scratches. The Si3N4 layer 29 is arranged at the outermost layer as a barrier to protect the entire film layer. The thickness of the thirteenth film layer 213 (Si3N4 layer) is 75-80nm, preferably 78nm.
[0037] The fourteenth film layer 214 (ZrO2 layer), i.e., the zirconium dioxide layer, serves as the seventh dielectric layer. ZrO2 is a material with high hardness, high density, and antioxidant properties, which can improve the physical properties and antioxidant properties of the film layer, thereby enhancing the strength of the Low-E glass, making the glass less susceptible to wear and scratches. The fourteenth film layer 214 (ZrO2 layer) and the thirteenth film layer 213 (Si3N4 layer) have an overlapping protection effect. The thickness of the fourteenth film layer 214 (ZrO2 layer) is 35 to 40 nm, preferably 38 nm.
[0038] The three-silver temperable three-property gray Low-E glass of the present application was tested, and the color performance of the glass obtained is shown in Table 1:
[0039] Color Performance parameter <![CDATA[Visible light transmittance T of glass vis > 65 <![CDATA[Visible light reflectance R of the glass surface out > 10 Glass surface color coordinate a* -0.5 Glass surface color coordinate b* -1.5 Film surface color coordinate a* -2.5 Film surface color coordinate b* -3.0
[0040] Table 1
[0041] It can be seen from Table 1 that the glass surface color coordinate a* of the present application is -0.5, the glass surface color coordinate b* is -1.5, the film surface color coordinate a* is -2.5, the film surface color coordinate b* is -3.0, and the Low-E glass as a whole presents a three-gray color, which increases the artistic effect of the Low-E glass, meets the aesthetic requirements of high-end buildings, improves the user experience, and improves the competitiveness of the product in the market.
[0042] In order to test the shielding and heat insulation effect of the triple silver tempered triple property gray Low-E glass of the present application, the triple silver tempered triple property gray Low-E glass of the present application was put on the UV-3600 ultraviolet spectrophotometer for testing and the following data were obtained. According to the JGJ / T 151-2008 standard, the optical and thermal properties of 6mm triple silver tempered Low-E+12A+6mm white glass were calculated, as shown in Table 2:
[0043] Performance Indicators parameter <![CDATA[Visible light transmittance T vis > 66 <![CDATA[Visible light reflectance R of the glass surface out > 14 <![CDATA[Solar transmittance T sol > 29 <![CDATA[Solar reflectance R out > 30 Heat transfer coefficient U 1.60 Shading coefficient Sc 0.38
[0044] Table 2
[0045] From the above Table 2, it can be seen that the visible light transmittance T of the triple-silver tempered triple-gray Low-E glass of the present application is vis is 66, the visible light glass surface reflectivity R out is 14, solar transmittance T sol is 29, the solar reflectivity R out The heat transfer coefficient U is 30, the heat transfer coefficient U is 1.60, and the shading coefficient Sc is 0.38. From the analysis of Table 2, it can be seen that a large amount of visible light can pass through the Low-E glass into the room, thereby increasing the indoor lighting effect. A large amount of solar energy is blocked to the outdoors, thereby preventing solar energy from entering the room and causing the indoor temperature to rise. Compared with the existing triple-silver glass, the triple-silver tempered tri-gray Low-E glass of the present application has better shading and heat insulation properties.
[0046] Specifically, the visible light transmittance T vis That is, the intensity of visible light passing through glass, the visible light glass surface reflectivity R out is the intensity of visible light reflected outside the glass, solar transmittance T sol is the intensity of solar energy passing through glass, solar reflectivity R out It is the intensity of solar energy reflected outside the glass. The heat transfer coefficient U represents the heat transfer intensity of the glass. The shading coefficient Sc is the ratio of the heat of solar radiation passing through the glass to the heat of solar radiation radiating to the glass. It represents the degree of attenuation of the heat transmitted by solar radiation by the glass without other shading measures.
[0047] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.
Claims
1. A three-silver temperable three-property gray Low-E glass, characterized in that: include: A glass substrate, wherein fourteen film layers are composited on the glass substrate in sequence from the inside to the outside, wherein the first film layer, i.e., the innermost film layer, is a ZrO2 layer, the second film layer is a Nb2O5 layer, the third film layer is an AZO layer, the fourth film layer is an Ag layer, the fifth film layer is a NiCr layer, the sixth film layer is an AZO layer, the seventh film layer is an Ag layer, the eighth film layer is a NiCr layer, the ninth film layer is an AZO layer, the tenth film layer is an Ag layer, the eleventh film layer is a NiCr layer, the twelfth film layer is an A ZO layer, the thirteenth film layer is Si3N4 layer, the fourteenth film layer is ZrO2, the thickness of the fourth film layer Ag layer is 9-12nm, the thickness of the fifth film layer NiCr layer is 1-3nm, the thickness of the seventh film layer Ag layer is 15-17nm, the thickness of the eighth film layer NiCr layer is 2.5-3.5nm, the thickness of the tenth film layer Ag layer is 3.5-5.5nm, and the thickness of the eleventh film layer NiCr layer is 2-4nm; The thickness of the first film layer, i.e., the innermost film layer, ZrO2 layer, is 35 to 50 nm, and the thickness of the fourteenth film layer, ZrO2 layer, is 35 to 45 nm; The thickness of the second film layer Nb2O5 is 11-13 nm; The thickness of the third film layer AZO layer is 5-7 nm; The thickness of the sixth film layer AZO layer is 110-115 nm; The thickness of the ninth film layer AZO layer is 40-43 nm; The thickness of the twelfth film layer AZO layer is 68-73 nm; The thickness of the thirteenth film layer Si3N4 is 75-80nm; Among them, the color coordinate a* of the glass surface of the three-gray color is -0.5, the color coordinate b* of the glass surface is -1.5, the color coordinate a* of the film surface is -2.5, and the color coordinate b* of the film surface is -3.0.
Citation Information
Patent Citations
Triple-silver low-emissivity coated glass and preparation method thereof
CN102898040A
Tri-silver LOW-E glass with neutral color and preparation method thereof
CN104310801A
Coated glass and preparation method thereof
CN105152549A
Double-silver low-emissivity coated glass
CN203567281U
Three-silver temperable three-property grey Low-E glass
CN211921327U